Anatomical reconstruction of proximal coronary artery stenosis in children. (12th May 2022) - Krokovay, A; Prêtre, R; Kretschmar, O; Knirsch, W; Valsangiacomo Buechel, E; Dave, H
Abstract: OBJECTIVES: Timing and method of surgical reconstruction for non-sclerotic proximal coronary artery stenosis, occurring de novo or post-coronary artery transfer, are evolving. We have pursued a technique of anatomical reconstruction of ostial and short segment proximal coronary artery stenosis and atresia in children, using patch plasty or interposition vein graft. Here, we discuss the medium- to long-term outcomes. METHODS: Nine consecutive children undergoing 10 left main coronary artery reconstructions using autologous great saphenous vein patch ( n = 4), autologous pericardium ( n = 4), xenopericardium ( n = 1) or great saphenous vein interposition graft ( n = 1) were retrospectively analysed. Complementary wedge resection of the stenotic coronary ostium was performed in chronic cases. RESULTS: The aetiology of coronary artery stenosis was post-arterial switch operation ( n = 6), Takayasu's arteritis ( n = 1), idiopathic left main coronary artery atresia ( n = 1) and anomalous origin of the left coronary artery from the pulmonary artery ( n = 1). The median age and weight at operation were 0.15 (range 0.01–13.1) years and 4.4 (range 3–13.1) kg, respectively. Survival was 100% at the medi follow-up of 12.6 (range 1–19.2) years. All patients showed normal left ventricular ejection fraction on transthoracic echocardiogram. In 1 patient, kinking of the proximal left circumflex artery resulted in non-significant obstruction. In all other cases, follow-up catheter angiography revealed unobstructed coronary arteries. Cardiac magnetic resonance tomography showed no significant perfusion deficit in any child. CONCLUSIONS: Anatomical reconstruction of the proximal left coronary artery using autologous saphenous vein may allow optimal restoration of physiological coronary blood flow, keeping the option of future coronary bypass operation open. Abstract : Coronary artery stenosis is rare in children.